Cascaded polarizer-PMF-Fabry–Pérot structure with a tunable initial state for ultra-highly sensitive temperature measurement. (24th October 2019) - Ruan, Tiantian; Xia, Li; Xia, Jianchun; Song, Yiming
Abstract: A reflective cascaded structure with a fiber Lyot filter and a Fabry–Pérot interferometer has been proposed and experimentally demonstrated for ultra-highly temperature measurement. The sensitivity of the sensor can be magnified to −31.4 nm °C −1 based on the Vernier effect, to our knowledge, which is the highest among all-fiber structures without other assisted coating or filling materials. The sensor possesses the remote sensing capability. Furthermore, the initial state can be tuned by loading strains on the Fabry–Perot cavity, so that the maximum sensing range is available at different initial temperatures, and then allowing the sensor to fulfill more practical application needs.